Learning through Leading: A Self-Study in District Administration. Issue 2 (3rd May 2016) - Collins, Christina
Abstract: There is little research in the area of understanding educational leaders' psychological processes. This lack of understanding leaves educational leaders to develop their own sense-making practices while in the complex and stressful act of leading. This self-study, conducted over more than half a school year in 2014–2015, was my own effort to do just that: to understand myself as a leader by examining various influences on my role using a four-quadrant framework for leadership. The findings highlight two significant areas influencing my leadership practices: the internal-entity quadrant, defined as the leader's personal values and beliefs, and the internal-context quadrant, defined as the leader's perception of the various contextual influences surrounding her role. Adopting this framework for my thinking allowed a more objective view of my practice and the beliefs and assumptions operating within my practice. While this work is, at a personal level, my own struggle to understand the complexities of leading, it is also examines one way in which district leaders might begin to think about their own sense-making practices using self-study methods.